2020
DOI: 10.1186/s12883-020-01701-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of MTHFR C677T gene polymorphism and its influence on the therapeutic effect of homocysteine in stroke patients with hyperhomocysteinemia

Abstract: Background: Hyperhomocysteinemia (HHCY) is a risk factor for cardiovascular and cerebrovascular diseases. The C677T 5, 10-methylenetetrahydrofolate reductase (MTHFR) gene polymorphism increases homocysteine (HCY) levels. This study analyzed the relationship between C677T MTHFR polymorphism and the therapeutic effect of lowering HCY in stroke patients with HHCY. Methods: Baseline data were collected from stroke patients with HHCY for this prospective cohort study. The C677T MTHFR genotype was detected by polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
3
1
1
Order By: Relevance
“…11; 15 The present study findings showed that the combined frequency of CT genotype was 14.4% from MTHFR C677T polymorphism. A slightly higher frequency found in previous studies among hyperhomocysteinemia with cardiovascular patients of CT genotype frequency as 23% in Pakistan, 16 30.4% in South India, 8 52% in West India, 31% in China, 17 and 41% in Italy. 18 Although these studies did not have the same comparator group as in the present study, which includes hyperhomocysteinemia among ischemic stroke between both vitamin and control, groups, which leads to variation in the frequency of MTHFR polymorphism.…”
Section: Discussioncontrasting
confidence: 51%
“…11; 15 The present study findings showed that the combined frequency of CT genotype was 14.4% from MTHFR C677T polymorphism. A slightly higher frequency found in previous studies among hyperhomocysteinemia with cardiovascular patients of CT genotype frequency as 23% in Pakistan, 16 30.4% in South India, 8 52% in West India, 31% in China, 17 and 41% in Italy. 18 Although these studies did not have the same comparator group as in the present study, which includes hyperhomocysteinemia among ischemic stroke between both vitamin and control, groups, which leads to variation in the frequency of MTHFR polymorphism.…”
Section: Discussioncontrasting
confidence: 51%
“…This polymorphism was significantly associated with ischemic stroke recurrence in our study. In various studies MTHFR polymorphisms were linked to elevated homocysteine levels 31 . Zhang et al suggest that hyperhomocysteinemia can predict the risk of stroke recurrence and mortality in patients with stroke 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In various studies MTHFR polymorphisms were linked to elevated homocysteine levels. 31 Zhang et al suggest that hyperhomocysteinemia can predict the risk of stroke recurrence and mortality in patients with stroke. 32 Previous studies have…”
Section: P-valuementioning
confidence: 99%
“…This result is consistent with previous reports. [27][28][29] One possible explanation is that the MTHFR C677T variant increases the risk of developing ischemic stroke, at least in part, by elevating homocysteine levels.…”
Section: Discussionmentioning
confidence: 99%